LAMP-assisted CRISPR-Cas12a platform for detection of Bacillus anthracis spores in environmental samples - Borse Rushikesh Sanjay; Maria Anto Dani Nishanth; Jess Vergis; Niveditha Pollumahanti; Laxman Chatlod; Yogesh Gadekar; M. Muthukumar; Baswa P. Reddy; Satya Veer Singh Malik; Sukhadeo Baliram Barbuddhe; Deepak Bhiwa Rawool (Analytica Chimica Acta, 2026)

Hydrogeochemical assessment and multivariate statistical analyses for the characterization of trace metals in groundwater of Chandragiri River Basin, Kerala, southwestern India - K.V. Sarath; E. Shaji; K.R. Adarshkrishna; P. Muthukumar; P.N. Renjith; V. Nandakumar (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Anti-Obesity Effect of Probiotic Carrot Nectar Incorporated with L. Plantarum MCC5231 - Aditi Goel; Md Touseef Khan; S. P. Muthukumar; Attar Singh Chauhan; Jyoti Prakash Tamang; Prakash. M. Halami (Probiotics and Antimicrobial Proteins, 2026)

Prevalence of emerging contaminants in the outlet of sewage treatment plants: an evidential report from Kerala, India with future concerns - Kochuparambil Ajayaghosh Akhilghosh; Athira Ramesh; Vijayalekshmi Padmachandran Aiswriya; Salman Farissi; P. S. Nishmitha; C. T. Aravindakumar; M. Thalamadai Karuppiah; Muthukumar Muthuchamy; Anbazhagi Muthukumar (Environmental Sustainability, 2026)

A critical review on technical advances and multifaceted role of carotenoids in human health with special emphasis on metabolic diseases - Sayani Roy; K. C. Dora; Siddhnath Kumar; Pooja Saklani; A. Muthukumar; Fatih Ozogul; K. C. Harisankar; R. D. Mutum; S. Celine Hilda Mary; V. K. R. Surasani; P. K. Dara (Phytochemistry Reviews, 2026)

Assessment of selected organic pollutants in sediments from a highly urbanized environment along the southeast coast of India - Muthukumar Chandrasekaran; Karthikeyan Panneerselvam; Kine Baek; Sissel B. Ranneklev; Merete Grung; Anders Ruus; Marianne Olsen; Vipin Babu. P; Ramu Karri; Tune Usha; M.V. Ramanamurthy (Marine Pollution Bulletin, 2025)

Peptide Epitope-Based Avian IgY Antibodies against SARS-CoV-2 Spike: A Cost Effective Approach for Viral Detection and Neutralization - G. N. Pramod; Prasan Havlad; Nalina Murthy; Abdul Majid; Jessie Thomas; M. Ghalib Enayathullah; Yogesh Sardana; P. K. Sreeram; S. P. Muthukumar; Tanaji Kudre; Pananghat Gayathri; Kiran Kumar Bokara; et al. (International Journal of Peptide Research and Therapeutics, 2025)

UAV-based herbicide application for efficient weed control and resource savings in direct-seeded rice - R. Arockia Infant Paul; P. Murali Arthanari; Panneerselvam Peramaiyan; Virender Kumar; Muthukumar Bagavathiannan; R. Sabarivasan (Crop Protection, 2025)

Low corrosive dual desiccant air conditioning: Antimicrobial activity, performance characteristics, and economic valuation with traditional VCRS - Juri Sonowal; P. Muthukumar; R. Anandalakshmi (Energy and Buildings, 2025)

Microplastics in water from the Cooum River, Chennai, India: An assessment of their distribution, composition, and environmental impact - J. Mohamed Afzal; S. Selvam; P. Saravanan; Priyadarsi D. Roy; P. Sanju; P. Muthukumar (Groundwater for Sustainable Development, 2024)

Capability of space borne multispectral image for detecting discoloration in optically complex coastal waters - Logesh Natarajan; Manigandan Vajravelu; Muthukumar Chandrasekaran; Sankar Ganesh Ramakrishnan; Thanamegam Kaviarasan; P. Vipin Babu; Sisir Kumar Dash; Karri Ramu; M.V. Ramana Murthy (Marine Pollution Bulletin, 2024)

Bisphenol A contamination in processed food samples: an overview - P. Kumar; R. S. Aruna Priyanka; P. Shalini Priya; B. Gunasree; S. Srivanth; S. Jayasakthi; A. Kapoor; R. MuthuKumar (International Journal of Environmental Science and Technology, 2023)

Evaluation of groundwater for nitrate and fluoride in Alappuzha region from the southwestern coast of India and associated health risks - S. Selvam; Akhila V. Nath; Priyadarsi D. Roy; K. Jesuraja; P. Muthukumar (Environmental Research, 2023)

Distribution and diversity of Fusarium oxysporum f.sp. cubense TR4 causing banana wilt in Sub-tropics of India and comparative analysis of TR4 specific molecular detection methods - Nidhi Kumari; Thukkaram Damodaran; Israr Ahmad; Shailendra Rajan; P. K. Shukla; Muthukumar Manoharan; Amar Kant Kushwaha; Haripal Singh; Ram Gopal; Sangeeta Kumari; Kavita Yadav; Popy Bora; et al. (Journal of Plant Biochemistry and Biotechnology, 2023)

Assessment of phytoplankton diversity, distribution, and environmental variables along the southeast coast of India - P. Sathish Kumar; G. Dharani; J. Santhanakumar; Dilip Kumar Jha; Vikas Pandey; S. Venkatnarayanan; J. Prince Prakash Jebakumar; C. Muthukumar; R. Arthur James (Frontiers in Marine Science, 2023)
Coastal waters are dynamic because of anthropogenic activities that contribute nutrients and contaminants. These changes have the potential to alter patterns of primary production and thus pelagic food webs. Here, we investigated the spatial variation of the phytoplankton community and its response to changing environmental variables at 84 stations along the five coastal districts of Tamil Nadu (TN). During the present study, 85 phytoplankton species were recorded, such as diatoms (64), dinoflagellates (18), silicoflagellates (1), and Cyanophyceae (2). The maximum phytoplankton abundance was recorded on the Thanjavur coast and gradually decreased towards the south coast of Tamil Nadu. Among the phytoplankton community, 50% was dominated by pennate diatoms, attributed to higher NO 3 − concentrations in the coastal waters due to agricultural discharge. Cluster analysis revealed that Ramanathapuram and Tirunelveli formed a closed cluster, whereas Thanjavur and Pudukottai formed a separate closed cluster associated with higher nutrient and metal concentrations, highlighting the difference in physicochemical parameters between the northern and southern districts of the TN coast. Relatively high nutrient concentrations in the coastal waters of northern districts are of greater concern, which could impact the coastal ecosystem. Coastal eutrophication is becoming a widespread phenomenon, causing disruption in the food chain and ecosystem balances and hence requiring regular monitoring and management.

Submarine groundwater discharge: An Asian overview - Sruthy Sajeev; P. Muthukumar; S. Selvam (Chemosphere, 2023)

Thermal performance and emission analysis of self-aspirated kerosene pressure stove with porous radiant burner using kerosene nanofuels - G. S. Sinha; N. Kumar Mishra; P. Muthukumar; M. Sharma (International Journal of Environmental Science and Technology, 2023)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

Numerical investigation on conventional and PCM heat sinks under constant and variable heat flux conditions - J. Sunku Prasad; R. Anandalakshmi; P. Muthukumar (Clean Technologies and Environmental Policy, 2021)

Strain-Specific Quantification of Native Probiotic Bacillus spp. and Their Effect on Liver Function and Gut Microflora of Experimental Rats - Papanna Shobharani; Serva P Muthukumar; Dhanya Kizhakayil; Prakash M Halami (Probiotics and Antimicrobial Proteins, 2019)

First report on wilt disease of mango caused by Ceratocystis fimbriata in Uttar Pradesh, India - P. K. Shukla; Savita Varma; Tahseen Fatima; Anju Bajpai; Rupesh Mishra; A. K. Misra; Gundappa; M. Muthukumar (Indian Phytopathology, 2018)

Global asymptotic stability of complex-valued neural networks with additive time-varying delays - K. Subramanian; P. Muthukumar (Cognitive Neurodynamics, 2017)

Characterisation of defatted Scenedesmus dimorphus algal biomass as animal feed - S. Vidyashankar; K. S. VenuGopal; V. S. Chauhan; S. P. Muthukumar; R. Sarada (Journal of Applied Phycology, 2015)

Performance investigation of high-temperature sensible heat thermal energy storage system during charging and discharging cycles - Hakeem Niyas; Likhendra Prasad; P. Muthukumar (Clean Technologies and Environmental Policy, 2015)

Mycorrhiza in sedges?an overview - T. Muthukumar; K. Udaiyan; P. Shanmughavel (Mycorrhiza, 2004)